Treatment outcomes of regimens containing delamanid within therapy of multiple and extensive drug resistant tuberculosis in the Russian Federation - A. O. Maryandyshev; S. M. Lorsanov; Z. B. Khaydarkhanova; S. B. Khunkarsultanov; D. V. Perkhin; O. M. Sveshnikova; A. I. Gayda; V. V. Privolnev (Туберкулез и болезни лёгких)
.